Fair Packaging and Labeling Act of 1966 (P.L. 89-759). (U.S. Congressional Research., 1966)
Outlines legislative history and provisions of P.L. 89-759, the Fair Packaging and Labeling Act, which establishes mandatory labeling standards for food and other commodities, and provides for voluntary adoption of packaging standards.